Hurthle cell carcinoma: a rare variant of thyroid malignancy (Bangladesh Journal of Medical Science, 2010)
Hurthle cell carcinoma is a rare entity of differentiated thyroid carcinoma. Modality of treatment is controversial due to the nature and rarity of the disease. However, total thyroidectomy followed by adjuvant treatment is prudent in this variant of thyroid malignancy in view of its aggressive nature. We report a case of Hurthle cell carcinoma of thyroid in an elderly male in which the pre operative diagnosis was follicular carcinoma. The outline of management is discussed. Keywords: Hurthle cell carcinoma; thyroid malignancy; management. DOI: 10.3329/bjms.v9i2.5659Bangladesh Journal of Medical Science Vol.09 No.2 Apr 2010 pp.103-106